A proposed guideline for vagus nerve stimulator handling in palliative care and after death. (28th May 2020) - Alhajaj, Ghadd; Atkinson, Jeffrey; Keezer, Mark R.; Nikolic, Ana; Myers, Kenneth A.
Abstract: Vagus nerve stimulation (VNS) is often used for patients with drug‐resistant epilepsy. Although this intervention may improve seizure control and mood, a number of factors must be considered when patients with VNS near end of life. We reviewed relevant literature to create a proposed guideline for management of patients with VNS in palliative care and after death. VNS has multiple possible side effects, including cough and swallowing difficulties. For patients with neurologic disease in palliative care, such adverse effects can severely affect quality of life and increase the risk for complications such as aspiration pneumonia. Patients with VNS should be screened regularly for such side effects, and VNS parameters should be adjusted if they are identified. If a patient requires urgent cardiac resuscitation involving external defibrillation, the VNS should be interrogated immediately afterwards to evaluate its function. During defibrillation, paddles should be placed perpendicular to the VNS, and as far as possible away from it. The VNS can be acutely turned off by taping the magnet to the patient's chest, thereby preventing any possible interference with restoration of a normal heart rhythm. After death, any staff involved with handling the body should be notified that a VNS is in place. The device must be removed prior to cremation, as it can explode with high heat. If the cause of death is unclear, a full postmortem examination should be undertaken, per sudden unexpected death in epilepsy guidelines. If there is concern about device malfunction, the device should be returned to the manufacturer for evaluation.